Decision to use herbicide in wheat production by the farm households in Nepal: A probit regression analysis - Adhikari, Surya P.; Ghimire, Yuga N.; Subedi, Sanjiv; Poudel, Hema K. (Journal of Agriculture and Natural Resources, 2020)
The use of herbicides in wheat production is increasing in Nepal mainly due to labor shortage and higher wage rates, even if available. However, little information is available on what factors determine the use of herbicides. This study explored the major factors that affect the decision to use herbicide by the wheat farmers. The semi-structured interview schedule was administered to 343 farmers from four major wheat-growing districts. The study employed a probit regression model to identify the factors that influenced the decision to use herbicides. Educations, membership, migration, wheat cultivated area, amount of urea use were identified as the significant factors influencing the decision of farmers to use herbicides. Herbicides user farmers produced 220 kg more wheat grain yield from one hectare of land compared to non-users. This study suggests that the wheat yield of Nepal could be increased through adopting better weed management techniques.